2012
DOI: 10.1099/ijs.0.027623-0
|View full text |Cite
|
Sign up to set email alerts
|

Carboxydocella manganica sp. nov., a thermophilic, dissimilatory Mn(IV)- and Fe(III)-reducing bacterium from a Kamchatka hot spring

Abstract: A thermophilic, anaerobic, dissimilatory Mn(IV)-and Fe(III)-reducing bacterium (strain SLM 61 T ) was isolated from a terrestrial hot spring on the Kamchatka peninsula. The cells were straight rods, 0.5-0.6 mm in diameter and 1.0-6.0 mm long, and exhibited tumbling motility by means of peritrichous flagellation. The strain grew at 26-70 6C, with an optimum at 58-60 6C, and at pH 5.5-8.0, with an optimum at pH 6.5. Growth of SLM 61 T was observed at 0-2.0 % (w/v) NaCl, with an optimum at 0.5 % (w/v). The genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…This wide distribution of dissimilatory Fe(III)-reducers in the bacterial and archaeal tree of life (Vargas et al, 1998;Weber et al, 2006) is compatible with the fact that iron is the fourth most abundant element in the Earth's crust. The Fe(III)-reducing thermophiles, including members of the domains 'Bacteria' and 'Archaea', are reported from marine hydrothermal environments, geothermally heated subsurface sediments (Slobodkin & Wiegel, 1997;Sievert et al, 1999;Slobodkin et al, 1999Slobodkin et al, , 2001Reysenbach et al, 2006;and others) and terrestrial hydrothermal environments (Kashefi et al, 2002;Slobodkina et al, 2012;Yoneda et al, 2012;and others). Iron has the potential to serve micro-organisms as an alternative electron acceptor for energy conservation when access to molecular oxygen is limited in these natural environments (Lovley & Phillips, 1986, 1988.…”
mentioning
confidence: 99%
“…This wide distribution of dissimilatory Fe(III)-reducers in the bacterial and archaeal tree of life (Vargas et al, 1998;Weber et al, 2006) is compatible with the fact that iron is the fourth most abundant element in the Earth's crust. The Fe(III)-reducing thermophiles, including members of the domains 'Bacteria' and 'Archaea', are reported from marine hydrothermal environments, geothermally heated subsurface sediments (Slobodkin & Wiegel, 1997;Sievert et al, 1999;Slobodkin et al, 1999Slobodkin et al, , 2001Reysenbach et al, 2006;and others) and terrestrial hydrothermal environments (Kashefi et al, 2002;Slobodkina et al, 2012;Yoneda et al, 2012;and others). Iron has the potential to serve micro-organisms as an alternative electron acceptor for energy conservation when access to molecular oxygen is limited in these natural environments (Lovley & Phillips, 1986, 1988.…”
mentioning
confidence: 99%
“…(Sung et al 2006), Bacillus infernus (Lovley 2000), Geothrix fermentans (Lovley 2000), Pantoea agglomerans (Francis et al 2000), Carboxydocella manganica (Slobodkina et al 2012), et (Table 1). However, there was less information available about an isolate previously obtained from skarn-type copper tailings.…”
Section: Characteristics Of Strain Cwmentioning
confidence: 98%
“…In addition to S°, common minerals capable of supporting microbial metabolism in hot springs include a variety of iron (hydr)oxides (Fig.1) (Fortney et al 2016;Inskeep and McDermott 2005;Kashefi et al 2008b;Langner et al 2001;Lovley et al 2004;Slobodkin 2005;Slobodkina et al 2012), which result from the oxidation of Fe(II) with oxygen (Inskeep et al 2004;Kozubal et al 2008). Dissimilatory iron reduction (DIR) plays a key role on the biogeochemistry of iron in both moderate and higher temperature environments (Lovley et al 2004) and has been suggested to be one of the earliest forms of microbial respiration (Vargas et al 1998).…”
Section: Geomicrobiology Of Fementioning
confidence: 99%